(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The Cloud Computing (CC) provides access to the resources with usage based payments model. The application service providers can seamlessly scale the services. In CC infrastructure, a different number of virtual machine instances can be created depending on the application requirements. The capability to scale Software-as-a-Service (SaaS) application is very attractive to the providers because of the potential to scale application resources to up or down, the user only pay for the resources required. Even though the large-scale applications are deployed on cloud infrastructures on pay-per-use basis, the cost of idle resources (memory, CPU) is still charged to application providers. The issues of saturation and wastage of cloud resources are still unresolved. This paper attempts to propose the resource allocation models for SaaS applications deployments over CC platforms. The best balanced resource allocation model is proposed keeping in view cost and user requirements.